2016
DOI: 10.3390/min6030088
|View full text |Cite
|
Sign up to set email alerts
|

Marine Phosphorites as Potential Resources for Heavy Rare Earth Elements and Yttrium

Abstract: Abstract:Marine phosphorites are known to concentrate rare earth elements and yttrium (REY) during early diagenetic formation. Much of the REY data available are decades old and incomplete, and there has not been a systematic study of REY distributions in marine phosphorite deposits that formed over a range of oceanic environments. Consequently, we initiated this study to determine if marine phosphorite deposits found in the global ocean host REY concentrations of high enough grade to be of economic interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…Other elements in high concentration in the phosphatized RGR crusts were Li (30.9-217, mean 127 ppm), which was much more enriched compared to the non-phosphatized crust, and the %HREY (29.1-50.2%, mean 40.8%), which was also very high compared to the non-phosphatized crusts and similar to the range determined for marine phosphorites by [49]. The highest individual REY concentrations were Ce (34.1-426, mean 195 ppm), Y (40.7-802, mean 237 ppm), La (23.0-370, mean 120 ppm), and Nd (16.1-324, mean 99.8 ppm).…”
Section: Phosphatized Fe-mn Crustssupporting
confidence: 79%
See 3 more Smart Citations
“…Other elements in high concentration in the phosphatized RGR crusts were Li (30.9-217, mean 127 ppm), which was much more enriched compared to the non-phosphatized crust, and the %HREY (29.1-50.2%, mean 40.8%), which was also very high compared to the non-phosphatized crusts and similar to the range determined for marine phosphorites by [49]. The highest individual REY concentrations were Ce (34.1-426, mean 195 ppm), Y (40.7-802, mean 237 ppm), La (23.0-370, mean 120 ppm), and Nd (16.1-324, mean 99.8 ppm).…”
Section: Phosphatized Fe-mn Crustssupporting
confidence: 79%
“…Substitution might also be the reason for HREY enrichments. Yttrium (Y 3+ ) and the REE 3+ replace Ca 2+ in the CFA structure [49,96], which is consistent with the positive correlation between the REY (excepting Ce) and P, especially for Y. [49] found that the %HREY of the total REY complement from seamount phosphorites is higher than in associated Fe-Mn crusts, due to different mechanisms of REE incorporation.…”
Section: Influence Of Phosphatization On the Chemical Composition Of supporting
confidence: 68%
See 2 more Smart Citations
“…Normalized to PAAS chemical microprobe analyses of DHR hydroxylapatite, indicate negative Ce anomaly [43]. The REE pattern is typical for seamount phosphorites (Figure 11; compare [108]), as well as land-based phosphorites. Besides hydroxylapatite, some traces of Y (24-44 ppm) were also identified in stratified phyllosilicates (glauconite, Fe-smectite and Fe-chlorite) and K-phillipsite (140-320 ppm).…”
Section: Phosphatesmentioning
confidence: 99%